1999
DOI: 10.1038/sj.mp.4000436
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and cytokine correlates of major depression and dysthymia with typical or atypical features

Abstract: Depression has been associated with both suppression and enhancement of various aspects of immune functioning. It was of interest to determine whether cytokine alterations associated with depression, including interleukin-1 (IL-1␤) and interleukin-2 (IL-2), were related to the neurovegetative symptom profile or to the chronicity of the illness. Circulating ACTH, cortisol, norepinephrine (NE) and epinephrine levels, and production of IL-1␤ and IL-2 from mitogen-stimulated lymphocytes were assessed in classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(156 citation statements)
references
References 39 publications
5
142
0
9
Order By: Relevance
“…This has not been described previously, to our knowledge. Abnormalities of cytokine activity in melancholia have been described (Anisman et al, 1999). However, the differences in PTX3 expression in the present experiment are not explainable by dissimilarities in plasma interleukins, since the fibroblasts from patients and controls were cultured in the same media.…”
Section: Discussionmentioning
confidence: 52%
“…This has not been described previously, to our knowledge. Abnormalities of cytokine activity in melancholia have been described (Anisman et al, 1999). However, the differences in PTX3 expression in the present experiment are not explainable by dissimilarities in plasma interleukins, since the fibroblasts from patients and controls were cultured in the same media.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have reported elevated TNFα levels in the blood and cerebrospinal fluid in patients with MDD (Dowlati et al., 2010; Goldsmith et al., 2016; Huang & Lee, 2007; Liu et al., 2012; Martinez, Garakani, Yehuda, & Gorman, 2012; Stelzhammer et al., 2011), but this finding was questioned in a recent meta‐analysis (Anisman et al., 1999). However, an elevated TNF‐α level has been somewhat associated with severe forms of depression (Anisman et al., 1999). Another meta‐analysis of inflammatory biomarkers in patients with MDD undergoing antidepressant treatment reported no decrease in the elevated baseline TNFα level.…”
Section: Discussionmentioning
confidence: 99%
“…Unless atypical depression is differentiated from depressed patients with neither melancholic nor atypical features, applying atypical criteria could be a cumbersome way of saying melancholia is not present. McGinn et al (1996), Anisman et al (1999), Fountoulakis et al (2004), Bruder et al (2002, Stewart et al (1998), andJoyce et al (2002), partially answered the challenge of Parker et al (2002) (see Table 6). All studies compared depressed patients having atypical features with other depressed patients, five including an undifferentiated group having neither melancholic nor atypical features.…”
Section: Summary Of Post-dsm-iv Validitymentioning
confidence: 94%
“…In addition, a concurrent comparison group with melancholic features would have allowed firmer inferences. Anisman et al (1999) investigated cortisol, ACTH, epinephrine, norepinephrine, and two cytokines (IL-1b and IL-2) in 74 depressed outpatients and 27 never depressed controls. The depressed subjects were assessed for the presence or absence of atypical features.…”
Section: Biological Studiesmentioning
confidence: 99%